2010
DOI: 10.1063/1.3465578
|View full text |Cite
|
Sign up to set email alerts
|

Observation of surface structure of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide using high-resolution Rutherford backscattering spectroscopy

Abstract: The surface structures of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C(n)MIM][TFSI], n=2,4,6) are studied by high-resolution Rutherford backscattering spectroscopy. The average composition of the surface molecular layer is very close to the stoichiometric composition, showing that neither ion is enriched in the surface layer. A detailed analysis indicates that both cations and anions have preferential molecular orientations at the surface. The alkyl chains of the [C(n)MIM] cations protrud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 38 publications
10
66
0
Order By: Relevance
“…However, in contrast to the UPS (He II) spectra the MIES difference spectrum reveals also a minor contribution from the F2p orbitals (Fig. 4 Notably, this interpretation, which is in our favor, is also in better agreement with the model of the surface structure given by K. Nakajima et al 36 obtained by their HRBS experiment. Moreover it is not in contradiction to the result that one or two trifluoro-group(s) of the anion point towards the vacuum.…”
Section: Ups Spectrasupporting
confidence: 80%
See 3 more Smart Citations
“…However, in contrast to the UPS (He II) spectra the MIES difference spectrum reveals also a minor contribution from the F2p orbitals (Fig. 4 Notably, this interpretation, which is in our favor, is also in better agreement with the model of the surface structure given by K. Nakajima et al 36 obtained by their HRBS experiment. Moreover it is not in contradiction to the result that one or two trifluoro-group(s) of the anion point towards the vacuum.…”
Section: Ups Spectrasupporting
confidence: 80%
“…Both ion pairs exhibit nearly the same relative geometry, where the nitrogen of the [Tf 2 N] À anion is used to form the connection to the mentioned most acidic hydrogen of the cation. A change in the preferred conformer of the [Tf 2 N] À anion at the surface depending on the alkylchain length of the cation was recently found by K. Nakajima et al 36 This fact was considered by the choice of an ion pair with a syn-conformer of the anion for [EMIm]Tf 2 N and one with the respective anti-conformer is chosen for [OMIm]Tf 2 N (see the displayed structure of the two utilized ion pairs in Fig. 1 52 have shown that the syn-conformer of the anion exhibits a slightly higher energy than the anti-conformer.…”
Section: Calculation Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…This directly observed near-surface ordering of the molecular moieties is consistent with the ordering deduced from indirect studies by surface tension and spectroscopy of ILs comprising [C n≥4 mim] + cations. Those measurements were interpreted as showing that the first layer of imidazolium rings and anions is located at a depth close to that of a fully extended C 18 chain (20,21) and that the alkyl chains protrude into the vapor (6,(22)(23)(24). The molecular model presented in Fig.…”
Section: Resultsmentioning
confidence: 99%